Vanuatu : Technical Assistance Report-Feasibility Study on the Introduction of Quarterly National Accounts. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2021)
The Vanuatu National Statistics Office (VNSO) requested a mission by the IMF's Pacific Financial Technical Assistance Centre (PFTAC) for conducting a feasibility study on the implementation of a quarterly national accounts (QNA) in Vanuatu. This study outlines the staff, organizational and data requirements for Vanuatu to implement a quarterly national accounts program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Vanuatu